How to Integrate the Concept of Deep Teaching into the Teaching of Values in Moral Education Course - Yuxian Zhu (Journal of Advanced Research in Education, 2024)
Moral education course plays a far-reaching leading role in cultivating students’ moral emotions, moral judgment, and moral behaviors. However, in actual class teaching, teachers often pay too much attention to the diversification of the form of teaching activities and neglect the exploration of knowledge deeply, which may easily lead to undesirable results including students’ shallow cognition, value orientation deviation, and so on. To solve this problem, this thesis will based on the concept of depth teaching and combined with the content of values, through clarifying the theoretical approach to integrate the concept of depth teaching into moral education and promoting the unity of the knowledge system and the value system, to realize the reconstruction of moral education curriculum.